Viral Enteric Infections in Acute Severe Ulcerative Colitis. (15th February 2022) - Ostrowski, Szymon; Croft, Anthony
Abstract: Background and Aims: Excluding superimposed enteric infection is critical in the management of acute severe ulcerative colitis [ASUC]. Whilst infection with Clostridium difficile and cytomegalovirus have been shown to increase colectomy and mortality rates, no data exist regarding the impact of common viral enteropathogens in ASUC. Our aim was to determine if viral enteric infection in ASUC alters the severity or outcomes of these episodes. Methods: This was a retrospective review of cases presenting to a large tertiary centre. Data were obtained from an in-house, prospectively maintained inflammatory bowel disease database. We identified all ASUC cases treated between October 2015 and January 2021 and compared those testing positive for adenovirus 40/41, human rotavirus or norovirus GI by faecal multiplex polymerase chain reaction [PCR] to those testing negative. Results: We identified 147 patients with ASUC and faecal multiplex PCR testing for viral pathogens. In total, 22/147 patients [14.9%] tested positive, two of whom tested positive for two viruses. The infected and non-infected cohorts did not differ significantly with regard to admission C-reactive protein [81.7 vs 76.6, p = 0.77], Mayo endoscopic subscore [2.4 vs 2.3, p = 0.43], length of hospital admission [7.9 vs 7.9 p = 0.99], requirement for rescue therapy [59% vs 56%, p = 0.75] or colectomy rate [4.5% vs 4.1%, p = 0.69]. Conclusions: Infection with viral enteropathogens was common in our ASUC cohort, but did not appear to affect disease severity at presentation, the need for rescue therapy or the success rate of rescue therapy.